Effects of Autumn Warming on Energy Consumption of Diapausing Fall Webworm (Lepidoptera: Arctiidae) Pupae. Issue 2 (3rd April 2021) - Zhao, Lvquan; Wang, Wei
Abstract: Since its invasion into China in 1979, the fall webworm, Hyphantria cunea Drury, has spread from Dandong city (about 40°N) in Liaoning Province to Nanjing city (about 32°N) in Jiangsu Province, and to other areas. Owing to geographic and latitudinal gradients in temperature, H. cunea will encounter temperature changes during the spreading process. In this study, we verified the hypothesis that autumn warming accelerates the energy consumption of H. cunea diapause pupae. We found that, after autumn warming, the body size and mass of diapause pupae decreased significantly and raised constant temperature accelerated carbohydrate and protein consumption in female pupae, while fluctuating temperature changes had a more pronounced effect on carbohydrate and protein consumption in male pupae. Contrary to expectations, the lipid content of diapause pupae did not decrease after autumn warming, and even increased significantly. We conclude that warming in autumn accelerates energy consumption by diapause pupae, and the autumn energy consumption of diapause pupae is dominated by carbohydrates, supplemented by protein when carbohydrates are overconsumed, while lipid use is dominated by anabolic metabolism during autumn.